Revised status of Schinia unimacula Smith including morphological comparisons with Schinia obliqua Smith (Lepidoptera: Noctuidae: Heliothinae) - Pogue, Michael G.; Harp, Charles E. (Zootaxa, 2003)
Schinia unimacula is resurrected from the synonymy of S. obliqua and is treated as a full species based on differences in maculation and male and female genitalic structures. Schinia coolidgei Hill remains a synonym of S. unimacula. Genitalia of both sexes of S. unimacula and S. obliqua are described and illustrated for the first time.